All Days 1990
DOI: 10.4043/6335-ms
|View full text |Cite
|
Sign up to set email alerts
|

Design of Submarine Pipelines Against Upheaval Buckling

Abstract: Thispaper describes part of a comprehensive joint-industry project on upheaval buckling.It develops a semiempirical simplified design method and detailed design methods based on a new numerical analysis, and illustrates their application by examples.It assesses alternative design strategies, and the implications of strain-based design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…A typical procedure in the engineering practice to calculate vertical driving forces during upheaval buckling was established by Palmer et al [6]. This procedure is considered semi-empirical and is appropriate for projects in the stage of FEED, FrontEnd-Engineering-Design (Thusyanthan et al [28]).…”
Section: Loading Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A typical procedure in the engineering practice to calculate vertical driving forces during upheaval buckling was established by Palmer et al [6]. This procedure is considered semi-empirical and is appropriate for projects in the stage of FEED, FrontEnd-Engineering-Design (Thusyanthan et al [28]).…”
Section: Loading Assessmentmentioning
confidence: 99%
“…This procedure is considered semi-empirical and is appropriate for projects in the stage of FEED, FrontEnd-Engineering-Design (Thusyanthan et al [28]). Analytical expressions presented in [6] followed the beam-column theory and the downward force per unit length (w D ) to keep the pipeline in equilibrium has to satisfy the equation:…”
Section: Loading Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The final configuration is shown on Figure 5. It is interesting to observe that this configuration is very similar to those observed on buried straight pipelines under an initial imperfection and constrained both laterally and axially by elastic foundation [6][7][8]. A direct method was used to solve Problem (P 2 ) in both Experiments 4 and 5, which in this case reduce to a system of linear equations.…”
Section: Solution Algorithmmentioning
confidence: 99%
“…The results showed a reduction in buckling temperature with the increased amplitude of the initial imperfection. Palmer et al [7] demonstrated through a small-scale test that the constraint of expansion of a pipeline due to the increasing internal pressure could induce vertical buckling. Peek and Yun [8] presented analytical expressions for triggering such lateral buckles by applying buoyancy to the pipeline.…”
Section: Introductionmentioning
confidence: 99%